Forewarned is forearmed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
In agriculture, as in life, prevention is better than cure. Studies show that for every dollar spent on disaster preparedness, between US$100 and US$1000 are needed after the event. ACP nations are learning to anticipate risk, rather than sit back and wai